2023
DOI: 10.1101/2023.11.24.568580
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A cholesterol switch controls phospholipid scrambling by G protein-coupled receptors

Indu Menon,
Taras Sych,
Yeeun Son
et al.

Abstract: Class A G protein-coupled receptors (GPCRs), a superfamily of cell membrane signaling receptors, moonlight as constitutively active phospholipid scramblases. The plasma membrane of metazoan cells is replete with GPCRs, yet has a strong resting trans-bilayer phospholipid asymmetry, with the signaling lipid phosphatidylserine confined to the cytoplasmic leaflet. To account for the persistence of this lipid asymmetry in the presence of GPCR scramblases, we hypothesized that GPCR-mediated lipid scrambling is regul… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…Although GPCRs are mainly known for their essential roles in signal transduction across the plasma membrane, recent in vitro studies [6, 7, 8] as well as molecular dynamics simulations [9] have revealed a moonlighting activity of these receptors: lipid scrambling. Flip-flops are rarely performed spontaneously due to the high energy barrier for the polar lipid headgroup to traverse the region of the non-polar tails.…”
mentioning
confidence: 99%
“…Although GPCRs are mainly known for their essential roles in signal transduction across the plasma membrane, recent in vitro studies [6, 7, 8] as well as molecular dynamics simulations [9] have revealed a moonlighting activity of these receptors: lipid scrambling. Flip-flops are rarely performed spontaneously due to the high energy barrier for the polar lipid headgroup to traverse the region of the non-polar tails.…”
mentioning
confidence: 99%